Analysis of the Operation of the Sectoral Planning Units Within the Latin American and Caribbean Agricultural Planning Process: Their participation in the agricultural sector's policy analysis and decision-making processes - Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, 2021)
152 Páginas